An exploratory study on the information needs and information seeking behavior of selected construction workers in Quezon City - Laurora, Marvic R.
Information is an invaluable and essential commodity in every people’s lives. People need information to develop their fullest potentials and skills by means of educating and equipping themselves with the proper knowledge and new learnings they acquire to become more successful in their job roles; to enrich their skills, and improve their quality of life. Construction workers offer their services by means of manual physical labor. Oftentimes, they are marginalized and underserved due to their illiteracy and as they term it, “no read, no write” making them vulnerable to be trapped in poverty. However, despite being under these circumstances, construction workers seek for valuable information pertaining to their job roles as they seek for career growth and self-improvement. They aim to prosper and excel in their line of work and improve their status in life, hence the need for them to find better employment opportunities offering higher salaries and wages or companies offering permanent employment and better benefits to workers like them, in spite of their age, education background or marital status.